2012
DOI: 10.1093/jac/dks023
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-resistant Shigella infections from Iran: an overlooked problem?

Abstract: This is the first known description of ESBL-producing and AmpC β-lactamase-producing Shigella and of PMQR Shigella in Iran. The emergence of CTX-15, CMY-2 and qnrS1 genes may compromise the treatment of shigellosis. Strategies to minimize the spread of ESBL-producing and AmpC-β-lactamase-producing Shigella should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
35
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 27 publications
11
35
2
Order By: Relevance
“…Every isolate that was resistant to chloramphenicol (26 of 47) was also resistant to the three other antibiotics above. These findings are consistent with recent observations in PNG and other low-income settings [24][25][26][27]. Multiple antibiotic resistance was also observed in S. Typhi.…”
Section: Discussionsupporting
confidence: 92%
“…Every isolate that was resistant to chloramphenicol (26 of 47) was also resistant to the three other antibiotics above. These findings are consistent with recent observations in PNG and other low-income settings [24][25][26][27]. Multiple antibiotic resistance was also observed in S. Typhi.…”
Section: Discussionsupporting
confidence: 92%
“…Also one S. sonnei isolate had CMY-59 gene. The ESBL-producing Shigella isolates in this study were higher than previous studies in other countries (Tajbakhsh et al, 2012). Therefore, the prevalence of ESBL-producing GNB in the central part of Iran was between 2.3% and 89.8% and the average prevalence of ESBL-producing GNB in the central part of Iran was 43.55% in hospitals and community samples.…”
Section: Central Part Of Irancontrasting
confidence: 63%
“…Another study that was conducted in a major pediatric hospital in Tehran showed that 4 out of 55 Shigella isolates, including three S. sonnei and one S. flexneri, had ESBL-positive phenotype (Tajbakhsh et al, 2012). Also one S. sonnei isolate had CMY-59 gene.…”
Section: Central Part Of Iranmentioning
confidence: 99%
“…Shigellosis is predominantly caused by S. sonnei in industrialized countries, whereas S. flexneri prevails in the developing world (17,18). In this study, S. sonnei (61.1%, n = 22) was the most common, followed by S. flexneri (27.8%, n=10), S. boydii (8.3%, n = 3), and S. dysenteriae (2.8%, n = 1).…”
Section: Discussionmentioning
confidence: 58%